Falls by individuals with chronic obstructive pulmonary disease: A preliminary 12‐month prospective cohort study. Issue 7 (23rd July 2015) - Oliveira, Cristino C.; Lee, Annemarie L.; McGinley, Jennifer; Thompson, Michelle; Irving, Louis B.; Anderson, Gary P.; Clark, Ross A.; Clarke, Sandy; Denehy, Linda
Abstract Background and objective Despite evidence of an increased fall risk in people with chronic obstructive pulmonary disease (COPD), there is a paucity of prospective fall data in this population. This preliminary study aimed to prospectively examine the prevalence rate, incidence rate and associated risk factors for falls in a sample of community‐dwelling people with COPD over 1 year. Methods Forty‐one participants with stable COPD (mean ± SD) aged 71 ± 8 years with a forced expiratory volume in 1 s of 45.1 ± 16.2% predicted were included. At baseline, participants' demographic, physical function and fall‐related measures were documented. Falls were monitored for 12 months following initial assessments. Results The prevalence of people having falls was 40% (95% CI: 24–56%); amongst these, 75% had frequent falls. The overall fall incidence rate was 1.17 falls/person‐year. Risk factors associated with a higher fall incidence rate ratio (IRR) in COPD were: number of pack‐years (IRR: 1.02; 95%CI: 1.00, 1.04), comorbidities (IRR: 2.02; 95%CI: 1.42, 3.06), number of medications (IRR: 1.15; 95%CI: 1.00, 1.34), history of falls in the previous year (IRR: 1.89; 95%CI: 1.10, 3.34), fear of falling (IRR: 1.08; 95% CI: 1.02, 1.14) and higher score in a fall risk assessment questionnaire for older adults (IRR: 1.14; 95% CI: 1.05, 1.25); P ≤ 0.05. When adjusted for age, only pack‐years (P = 0.01), number of comorbidities (P < 0.001) and history of falls (P = 0.03) were related to an increased fall incidence. Conclusions These preliminary findings demonstrated the fall prevalence and incidence rate in community‐dwelling people with stable COPD and identified prospective risk factors for an increased fall incidence, which suggest potential mitigation strategies.